ANALISIS HUKUM ALIH FUNGSI TANAH PERTANIAN MENJADI PEMBANGUNAN PERUMAHAN DAN PEMUKIMAN (STUDY DI KABUPATEN BIMA) - nurmi, siti; arba, Arba; Putro, Widodo Dwi (Jurnal Dinamika Sosial Budaya, 2020)
This study aims to examine the legal analysis of the conversion of agricultural land into housing development in Kabupaten Bima. This research is structured as an empirical legal research based on the consideration that this research in problem analysis is carried out by combining secondary and primary legal materials obtained in the field. The approach used is the statute approach, conceptual approach, and the sociological approach to law. Based on the results of the study, it can be concluded that the mechanism for changing the function of agricultural land into housing development is divided into two mechanisms, namely through a location permit if the land requested is more than 10,000 m2 while the land use change permit is used if the land use is less than 10,000 m2. With the provision that a treatise is required for technical land considerations issued by the National Land Agency of Bima Regency and a decision from the regional spatial planning coordination team regarding recommendations for space utilization permits for housing development. The policy issued by the Bima regency government is to become a reference in the conversion of land functions in line with the main agrarian law regulations and regional regulations on the spatial plan for the Bima district.